childhood, ethics and amorousness in the learning experience - gomes, lisandra ogg; lopes, sammy william (childhood & philosophy, 2016)
In this text, we present reflections and analyses based on the philosophical and sociological fields about the childhood education, taken from the relation among the concepts of ethics, esthetics, affect and amorousness. Initially, we postulate that education of children should involve, necessarily, the collective conception of an ethical and affective curricular plan, able to welcome and to explore the vital force of childhood as a fundamental educational component. Thus, we evaluated as essential to the achieving of this affective learning mode, the constitution of a differential modality of amorous interactions (either between children and adults, whether among themselves, and from them to the world and the life), capable of engendering the singularity through which the ethical-aesthetic and political movement of an education for the childhood’s potency can be conceived. From these referrals, we dedicate to the drawing of the basic principles able to sign a possible conceptual image for an ethical-affective children’s education. This education is oriented to take on the children’s playing as a pure plan of the uneven experimentation, opened to the come-to-be indetermination’s forces - inherent to the sensitive, imaginative and intellectual relations - that articulate social and culturally the act of learning and teaching. Our effort was to put in discussion the imperatives of an education based on precepts and practices that try not to eliminate or minimize, but to establish a positive, attentive and sensitive relationship with the differences that childhood and children forcibly impose on us.